DAMPAK WISATA HIU PAUS DI BOTUBARANI PADA SOSIAL BUDAYA MASYARAKAT PESISIR - Masruroh, Masruroh; Eraku, Sunarty Suly; Bano, Multiyawati; Ismail, Rumiyati; Ramadhan, Mohammad (Jurnal Samudra Geografi, 2024)
This whale shark tourism is the best tourism in Gorontalo province, this tourism attracts many tourists to visit and enjoy the beach. This study aims to determine the impact of whale shark tourism on the socio-culture of coastal communities. The method used in this study is a quantitative approach with data collection through a questionnaire survey. The results of the study showed an increase in the community's economy by 20-30% from 70% of respondents who answered the questionnaire survey. For environmental awareness, the community participated in conservation, as many as 60% of respondents were active in environmental conservation programs after participating in whale shark tourism socialization. Changes in social norms 40% of respondents experienced changes in traditions and social norms due to interactions with tourists and environmental conditions 55% of respondents were aware of an increase in environmental pollution and pressure on natural resources since whale shark tourism was opened. So it can be concluded that there are positive and negative impacts including increasing community economic income, increasing awareness of environmental conservation, changes in local cultural values ​​and pressure on natural resources.